THU0042 Longitudinal IP-10 serum levels associate with the course of disease activity and achieving dmard-free sustained remission in rheumatoid arthritis. (15th June 2017) - Hooij, A van; Boeters, D; Fat, E Tjon Kon; Eeden, S van den; Corstjens, P; Mil, A van der Helm-van; Geluk, A
Abstract : Background: Although rheumatoid arthritis (RA) is a chronic autoimmune disease that is persistent in the majority of patients, 10–15% of the RA patients achieve disease modifying anti-rheumatic drugs (DMARD)-free sustained remission over time. Biological mechanisms underlying the persistence of inflammation in RA are yet unidentified. It is well established that increased serum levels of IFN-γ-induced protein 10 (IP-10) are associated with (acute) increased inflammatory responses against mycobacterial pathogens causing leprosy and tuberculosis, thereby providing useful diagnostic tools in these infectious diseases. Based on previous genetic susceptibility studies, we hypothesize that there is an overlap between inflammatory responses observed in these mycobacterial diseases and those observed in RA. Therefore, we determined the association between serial IP-10 serum levels and achieving DMARD-free sustained remission as well as disease activity scores (DAS)-remission. Objectives: To 1) assess the association between IP-10 levels over time in patients that have persistent RA versus patients that achieve DMARD-free sustained remission, and 2) determine the association between IP-10 levels and DAS. Methods: 139 serum samples of 34 RA-patients (1987-criteria), obtained at the time of diagnoses and at yearly intervals thereafter, were studied. 15 patients had persistent RA and 19 patients achieved DMARD-free sustained remission after a median follow up of 2.7 years. IP-10 serum levels were measured using a previously developed, user-friendly lateral flow assay. Baseline and change in IP-10 levels over time were compared between patients with persistent RA and those achieving DMARD-free sustained remission. The association between the change in IP-10 level and the change in DAS was studied; in addition the course of the absolute IP-10 levels and the DAS over time was plotted for individual patients. Results: IP-10 serum levels varied from 316 – 53, 685 pg/ml between RA-patients. Patients that had persistent arthritis or achieved DMARD-free sustained remission over time did not differ in baseline IP-10 levels (median persistent RA 1991 pg/ml and median DMARD-free sustained remission 3292 pg/ml, p=0.19). However, a significant decrease in IP-10 levels over time was observed in patients achieving DMARD-free sustained remission (p=0.003), whereas IP-10 levels remained stable in patients with persistent RA. Changes in IP-10 levels correlated well with changes in DAS scores (p=0.05). Also at the level of individual patients, a strong correlation between IP-10 levels and DAS over time was observed. Conclusions: These longitudinal data indicate that IP-10 levels are associated with perseverance of RA as well as with disease activity. Rapid diagnostic tests measuring IP-10 levels can therefore be helpful in monitoring of RA patients. Disclosure of Interest: None declared